2021
DOI: 10.1038/s41598-021-82742-y
|View full text |Cite
|
Sign up to set email alerts
|

Foxes fertilize the subarctic forest and modify vegetation through denning

Abstract: Ecosystem engineers modify habitats through processes other than trophic interactions, such as by regulating soil nutrients, and can influence resource availability and quality for other organisms. Predator-mediated elemental cycling may be especially important in determining plant diversity and growth in ecosystems where soil fertility and primary productivity are low. Red foxes (Vulpes vulpes L.), top predators in the Subarctic, could engineer local ecosystems through denning, which could create biogeochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Arctic foxes re-use dens for decades or even centuries (Macpherson 1969), and through time the combination of digging burrows and the accumulation of nutrients from fox excrement and prey remains likely alters local vegetation. As noted earlier, similar nutrient-enhancement patterns are found on other predator home sites (Kurek et al 2014;Fedriani et al 2015;Kucheravy et al 2021;Lang et al 2021), supporting the hypothesis that the predators are the cause of the enhanced vegetation. Arctic foxes, and other predators, have accordingly been classified as ecosystem engineers -organisms that benefit other species through physical modifications of their environment (Jones et al 1994) -due to the unique vegetative traits localized to their dens.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Arctic foxes re-use dens for decades or even centuries (Macpherson 1969), and through time the combination of digging burrows and the accumulation of nutrients from fox excrement and prey remains likely alters local vegetation. As noted earlier, similar nutrient-enhancement patterns are found on other predator home sites (Kurek et al 2014;Fedriani et al 2015;Kucheravy et al 2021;Lang et al 2021), supporting the hypothesis that the predators are the cause of the enhanced vegetation. Arctic foxes, and other predators, have accordingly been classified as ecosystem engineers -organisms that benefit other species through physical modifications of their environment (Jones et al 1994) -due to the unique vegetative traits localized to their dens.…”
Section: Introductionsupporting
confidence: 85%
“…For instance, predators that perennially re-use home sites may indirectly affect local plant and soil communities by concentrating prey-derived nutrients there. Soil nutrient levels and plant growth are greater at ground-nesting eagle owl ( Bubo bubo ) nests compared to reference sites (Fedriani et al 2015), whereas the combination of bioturbation (from digging burrows) and nutrient deposition by badgers ( Meles meles ) and red foxes ( Vulpes vulpes ) benefits plants around their dens (Kurek et al 2014; Kucheravy et al 2021; Lang et al 2021). To date, few studies have looked at these patch-scale predator effects from a landscape-scale perspective (but see Bump et al 2009; Gable et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In each of our models, denning was a significant predictor of ring width, with higher radial growth in white spruce on dens between 1897 and 2017 at treeline, despite similarities in tree densities, climate, and age across all sites. Our previous work found that red fox dens were dominated by tall, erect shrubs, grasses, and forbs, whereas control sites are mainly dominated by prostrate shrubs, which we attributed to the higher nutrient concentrations on dens (Lang et al, 2021). The nutrients added by red foxes likely also resulted in the higher radial growth observed in white spruce.…”
Section: Discussionmentioning
confidence: 74%
“…Red foxes ( Vulpes vulpes ) are widely distributed worldwide (Larivière & Pasitschniak‐Arts, 1996) and are considered ecosystem engineers by concentrating soil nutrients through organic waste, depositing prey remains, and disturbing soils at den sites (Godó et al, 2018; Kurek et al, 2014; Lang et al, 2021). These activities alter vegetation composition on dens compared to the surrounding habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation